TRAINING NEEDS OF RURAL WOMEN IN ERI CULTURE IN ASSAM PROVINCE (Global Journal of Human-Social Science, 2010)
Rural women in Assam are actively involved in eri culture and being considered it as a subsidiary occupational venture. The women farmers are generally traditionally bound in respect of knowledge and skills being used in eri culture. Hence, imparting training of women on improved practices of eri culture is exist as a gap to be filled. Training is an effective tool for improving ability of the women to do their vocation more efficiently. A good understanding of needs of the farmers is fundamental to make the training programme successful and hence, an assessment of the needs of the farmers was made in the year 2008 for designing the relevant means of training to meet them. The study has also focused on level of knowledge and skills of the women farmers in different activities of eri culture. From the study, it could be observed that majority of the women involved in spinning of eri silk (92.7%) followed by silkworm egg production and silkworm rearing (86.0%), marketing of produces( 74.0%) and disinfection of rearing house and rearing appliances (45.3%). Involvement of women in host plant cultivation and management was found very less (4.0%). The study also inferred that level of knowledge and skills of the women farmers was considerably low and the training need was more prominent almost in all the improved practices. The women desired to have practical training at the Research Institute for a period of one or two weeks with the facilities like free boarding, stipend, transportation, exposure visit and teaching through audio-visual aids using local language.